(untitled) (Semiárida, 2025)
The RIZOBIOS-2025 Seminar-Workshop, titled ’One hundred thirty years of legume inoculation with rhizobia: Where are we now and how do we proceed?’, was held virtually on June 18 and 19, 2025. The event was organized by the National Institute of Agricultural Technology (INTA), the National University of La Pampa (UNLPam), and the National University of Rosario (UNR). It gathered over 500 participants (registered) from 23 Argentine provinces and several countries in Latin America and Spain. On the first day, the history and current state of legume inoculation—such as soybean, vetch, peanut, and alfalfa—in Argentina, Uruguay, and Brazil were explored. The program also focused on inoculant evaluation, addressing methodologies for microbiological quality control, biological activity, and agronomic validation. The second day concentrated on technical aspects, such as the counting of viable rhizobia in inoculants and the current MERCOSUR regulations for their registration and commercialization. The closing session presented a market analysis and production technologies in the region. A survey of the registrants revealed a heterogeneous adoption of this technology, with a generally very positive perception, highlighting benefits such as cost reduction, improved fertilizer use efficiency, and being an essential tool for climate change mitigation and adaptation. However, the need for further training in inoculation techniques and a greater focus on the quality control of inoculants was identified. RIZOBIOS-2025 marked a turning point towards the future of inoculants, outlining opportunities to consolidate the practice of inoculation as an effective tool for modern, productive, and environmentally responsible agriculture.